A simple monoselective C–H oxygenation approach for the synthesis of ursane triterpenoids. Issue 7 (23rd January 2023) - Mei, Wenyi; Fan, Sisi; Han, Yufei; Shi, Cunjian; Qiu, Lijie; Shen, Yunheng; Zhao, Zhenjiang; Xu, Yufang; Li, Honglin
Abstract : The total syntheses of six ursane triterpenoids have been realized from ursolic acid via a simple monoselective C–H oxygenation approach. Abstract : Herein, we presented a simple approach for C–H oxidation in the C23 or/and C24 of ursane triterpenoids without any protection of a Δ 12, 13 double bond. As a result, from commercial ursolic acid (UA), six naturally occurring ursane triterpenoids were synthesized in overall yields of 3.4% to 36.8%, which implied the importance of this approach for the derivation of natural products and their application in biological activity.